PENGARUH PARTISIPASI MASYARAKAT DAN KINERJA TIM SWAKELOLA TERHADAP EFEKTIVITAS PRODAMAS DI KELURAHAN REJOMULYO KOTA KEDIRI - Mohamad Rizky Zakaria (Universitas Islam Kadiri, 2019)
Participatory development model can be regarded as a form of development management that prioritizes the community active participation in every stage of development. Facilitation Program for Community Empowerment or abbreviated PRODAMAS adopted the participatory development model in which public participation was a prerequisite to run this program. Facilitation Program for Community Empowerment (PRODAMAS) in Rejomulyo Kediri implemented by involving the community to be involved in the planning, implementation, utilization and evaluation of development programs. The purpose of this research are to: 1) Determine the influence of public participation in the effectiveness PRODAMAS in Rejomulyo Kediri, 2) Determine the influence self-management team performance to the effectiveness of PRODAMAS in Rejomulyo Kediri, and 3) Determine the influence of community participation and self-management team performance collectively to the effectiveness of PRODAMAS in Rejomulyo Kediri. The method used in this research is descriptive and correlational quantitative research approach. Descriptive method is used to describe the condition of each variable. The correlation method is used to determine the relationship of independent and dependent variables. The data analysis used is descriptive analysis, multiple linear regression analysis, hypothesis testing simultaneously (f-test), partial hypothesis test (t-test), and the coefficient of determination. The sampling technique used is saturated samples where the entire population sampled. Based on the data analysis, showed that the variables of community participation and self-management team performance either partially or collectively have a positive and significant impact to the effectiveness of PRODAMAS in Rejomulyo Kediri.